MAKNA MISA ONLINE DAN MEDIA DIGITAL SEBAGAI SARANA BERPASTORAL DI TENGAH PANDEMI COVID-19 - Maria Fransiska Dilgan Bewoli; Maria Rivandus Senang (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2022)
This article focuses on a review of the meaning of online. mass and digital media as a means of pastoralism amid the Covid-19 pandemic. The main problem discussed is the phenomenon that there are still many people who have doubts about the meaning of online. mass as a means of pastoralism during the Covid-19 pandemic. However, from a different perspective, the Church sees that digital media is a gift from God that can be a means and intermediary in special situations experienced by the people, such as during this pandemic. This article aims to find the right picture of the meaning of online. mass and the use of digital media as a means to help carry out pastoral activities during the Covid-19 pandemic. By using library methods and document studies, the authors conclude that the meaning of online. mass is very varied because it all depends on the inner disposition of everyone who experiences it and digital media is seen as a means to answer the faith needs of the people in the midst of the Covid-19 pandemic.